2015
DOI: 10.1073/pnas.1506458112
|View full text |Cite
|
Sign up to set email alerts
|

Retinal waves regulate afferent terminal targeting in the early visual pathway

Abstract: Current models of retinogeniculate development have proposed that connectivity between the retina and the dorsal lateral geniculate nucleus (dLGN) is established by gradients of axon guidance molecules, to allow initial coarse connections, and by competitive Hebbianlike processes, to drive eye-specific segregation and refine retinotopy. Here we show that when intereye competition is eliminated by monocular enucleation, blocking cholinergic stage II retinal waves disrupts the intraeye competition-mediated expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
(133 reference statements)
0
10
0
Order By: Relevance
“…1a ). We chose this time point as it has been previously shown that the expansion of the ipsilateral projection is retinal wave-dependent between P5 and P10 [ 8 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1a ). We chose this time point as it has been previously shown that the expansion of the ipsilateral projection is retinal wave-dependent between P5 and P10 [ 8 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that retinal waves are critical for the targeting of retinogeniculate afferents following the removal of competing inputs to the dLGN [ 8 ]. While this work demonstrated that aspects of afferent terminal targeting during retinogeniculate refinement are retinal wave-dependent, it remained unclear what retinal wave properties might be necessary for this process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new insight into how waves influence eye-specific segregation in ferrets was achieved using an enucleated ferret model (Failor et al, 2015 ). Monocular enucleation results in expanded ipsilateral projections in the dLGN.…”
Section: Inter-eye Competition Instructs Eye-specific Segregationmentioning
confidence: 99%